Crystal structure of Bacillus anthracis virulence regulator AtxA and effects of phosphorylated histidines on multimerization and activity. Issue 3 (30th December 2014) - Hammerstrom, Troy G.; Horton, Lori B.; Swick, Michelle C.; Joachimiak, Andrzej; Osipiuk, Jerzy; Koehler, Theresa M.
Summary The Bacillus anthracis virulence regulator AtxA controls transcription of the anthrax toxin genes and capsule biosynthetic operon. AtxA activity is elevated during growth in media containing glucose and CO2/bicarbonate, and there is a positive correlation between the CO2/bicarbonate signal, AtxA activity and homomultimerization. AtxA activity is also affected by phosphorylation at specific histidines. We show that AtxA crystallizes as a dimer. Distinct folds associated with predicted DNA‐binding domains (HTH1 and HTH2) and phosphoenolpyruvate: carbohydrate phosphotransferase system‐regulated domains (PRD1 and PRD2) are apparent. We tested AtxA variants containing single and double phosphomimetic (His→Asp) and phosphoablative (His→Ala) amino acid changes for activity in B. anthracis cultures and for protein–protein interactions in cell lysates. Reduced activity of AtxA H199A, lack of multimerization and activity of AtxAH379D variants, and predicted structural changes associated with phosphorylation support a model for control of AtxA function. We propose that (i) in the AtxA dimer, phosphorylation of H199 in PRD1 affects HTH2 positioning, influencing DNA‐binding; and (ii) phosphorylation of H379 in PRD2 disrupts dimer formation. The AtxA structure is the first reported high‐resolution full‐length structure of a PRD‐containing regulator, and can serve as a model for proteins of this family, especially those that link virulence to bacterial metabolism.